Usher syndrome type I associated with bronchiectasis and immotile nasal cilia in two brothers. Issue 3 (March 1993) - Bonneau, D; Raymond, F; Kremer, C; Klossek, J M; Kaplan, J; Patte, F
Abstract : Usher syndrome type I is an autosomal recessive disease characterised by congenital sensorineural deafness, involvement of the vestibular system, and progressive visual loss owing to retinitis pigmentosa. Here we report the association of this disease with bronchiectasis, chronic sinusitis, and reduced nasal mucociliary clearance in two sibs and we suggest Usher syndrome type I could be a primary ciliary disorder.